Cryptocurrency in Islamic Economics: A Critical Analysis of Dogecoin’s Compliance with Sharia Principles - Qiestha Khaira, Haba; Irawan, Anggi; Tamam, Munjir (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the characteristics of Dogecoin within the framework of Islamic economics, assessing its compliance with principles such as fairness, transparency, and the prohibition of gharar, maisir, and riba. The research aims to determine whether Dogecoin can function as a legitimate medium of exchange under Islamic financial ethics. A descriptive-analytical approach is employed, focusing on key aspects of Dogecoin, including its volatility, anonymity, and transactional utility. The analysis is grounded in Islamic economic principles, evaluating the extent to which Dogecoin aligns with or deviates from these ethical and legal standards. The findings indicate that while Dogecoin leverages blockchain technology to provide transparency and enhance financial inclusion, its high market volatility and speculative nature pose challenges to meeting Islamic economic principles. These factors contribute to uncertainty (gharar) and speculative risk (maisir), raising concerns about its permissibility in Islamic finance. This study contributes to the discourse on cryptocurrency in Islamic economics by offering a focused analysis of Dogecoin, a digital asset often overlooked in scholarly discussions. It provides a nuanced evaluation of how emerging financial technologies interact with Islamic financial ethics. The study underscores the need for Islamic-based regulatory frameworks and financial literacy initiatives to ensure responsible engagement with cryptocurrencies. Policymakers and scholars must work toward guidelines that balance innovation with ethical considerations, fostering a financial environment that aligns with Islamic values.